Validity and reliability questionnaire test of knowledge, Attitudes, and behavior on dengue fever prevention - Anggraini, Fitria Dewi Puspita; Aprianti, Aprianti; Muthoharoh, Nor Amalia; Permatasari, Indah; Azalia, Jihan Listu (Institute of Accounting Research and Novation (IARN), 2023)
It is necessary to have standardized instruments that validity and reliability to ensure the data to be collected. This research to test the validity and reliability of the knowledge, attitude and behavior questionnaire on dengue fever prevention. This study used a quantitative method with a cross sectional design. The population were patients with diagnoses of DD, DHF, and DSS based on Rowosari Health Center medical record data for January 2022-January 2023 as many as 248 people. The samples taken were 30 people from Tembalang, Meteseh, Bulusan and Kramas Villages by simple random sampling methode. Data collection was carried out using a questionnaire. Validity test is done by Pearson Product Moment test. The questionnaire valid if the r count value is > from r table with a correlation value > 0,361. The reliability test was declared reliable if value >0,600 with Cronbach's Alpha analysis. Result for knowledge, attitude and behavior questionnaire item are 16 from 20 statements, 14 from 15, and 9 from 10 statements item are valid with R Count Pearson Correlation Value > 0,361. Test the reliability of knowledge, attitude and behavior variables with Cronbach's Alpha value of 0,774 ; 0,815 and 0,818 > 0,600 so that all statement items are reliable. Questionnaire can be used as a reference to measure knowledge, attitude and behavior on dengue fever prevention